In vitro assessment of 39 CYP2C9 variants found in the Chinese population on the metabolism of the model substrate fluoxetine and a summary of their effects on other substrates. (17th April 2015) - Ji, Y.; Chen, S.; Zhao, L.; Pan, P.; Wang, L.; Cai, J.; Dai, D.; Hu, G.; Cai, J. P.; Huang, H.
Summary: What is known and objective: Cytochrome P450 2C9 (CYP2C9) is a polymorphic enzyme that is responsible for clearing approximately 15% of clinically important drugs. The objective of this study was to assess the catalytic characteristics of 39 CYP2C9 isoforms found in the Chinese population and their effects on the metabolism of the model substrate fluoxetine in vitro . Methods: Baculovirus‐mediated expressing system was used to highly express wild‐type and the 38 CYP2C9 allelic variants in insect cell microsomes. Then, the enzymatic characteristics of each variant were evaluated using fluoxetine as the substrate. Reactions were performed at 37 °C with the insect microsomes and 10–200  μ m fluoxetine for 60 min. After termination, the products were precipitated and used for signal collection by UPLC–MS/MS. Results and discussion: Of the 39 tested CYP2C9 isoforms, only four variants (CYP2C9*3, CYP2C9*27, CYP2C9*34 and CYP2C9*37) exhibited similar relative clearance values to that of the wild‐type CYP2C9*1. Moreover, five variants (CYP2C9*14, CYP2C9*36, CYP2C9*45, CYP2C9*48 and CYP2C9*55) showed a higher intrinsic clearance value than the wild‐type protein, whereas the remaining 29 CYP2C9 isoforms exhibited significantly decreased clearance values (from 6·23% to 87·74%) compared to CYP2C9*1. In addition, 28 CYP2C9 isoforms including CYP2C9*3 exhibited a trend towards substrate inhibition for fluoxetine. What is new and conclusion: This study provides the most comprehensive data on the enzymatic activities associated with all reported CYP2C9 variants in the Chinese population with regard to the widely used antidepressant drug, fluoxetine. Our data indicate that more attention should be paid to subjects carrying the corresponding infrequent CYP2C9 alleles when administering fluoxetine in the clinic. Abstract : This study provides the most comprehensive data on the enzymatic activities associated with all reported CYP2C9 variants in the Chinese population with regard to the widely used antidepressant drug, fluoxetine. Our data indicate that more attention should be paid to subjects carrying the corresponding infrequent CYP2C9 alleles when administering fluoxetine in the clinic.